2001
DOI: 10.1007/s001980070021
|View full text |Cite
|
Sign up to set email alerts
|

High-Impact Exercise and Bones of Growing Girls: A 9-Month Controlled Trial

Abstract: The maximum amount of bone a person can obtain during the first two decades of life is an important determinant of bone mass in later life, and an increase in peak bone mass has been associated with decreased risk for osteoporotic fractures. It is known that growth of bone and thus development of peak bone mass are strongly controlled by genetic factors, but information on the role of environmental factors, such as exercise and nutrition, (e.g., exercise) on growing bone is limited. We tested a hypothesis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
233
2
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(258 citation statements)
references
References 38 publications
(56 reference statements)
16
233
2
7
Order By: Relevance
“…This finding suggests a potential for the gymnastics loading stimulus to be overriding the natural tendency for later-maturing individuals to have less bone mass in young adulthood. However, it should also be noted that other studies suggest bone may be most responsive to mechanical loading before puberty, (42,43) which was when the current cohort was actively training.…”
Section: Discussionmentioning
confidence: 81%
“…This finding suggests a potential for the gymnastics loading stimulus to be overriding the natural tendency for later-maturing individuals to have less bone mass in young adulthood. However, it should also be noted that other studies suggest bone may be most responsive to mechanical loading before puberty, (42,43) which was when the current cohort was actively training.…”
Section: Discussionmentioning
confidence: 81%
“…(3) However, of the four school-based exercise interventions that used pQCT to assess bone geometry, all failed to observe any significant exercise-induced benefits on measures of tibial bone structure, (6,(26)(27)(28) which may relate to the relatively short duration of these trials (9 to 16 months). In contrast, we observed that our 4-year generalized PE program focusing on core movements, coordination and agility, skill activities, movement challenges and games, and dynamic movement control improved midshaft cortical area and/or thickness in young girls and boys, but this did not translate into greater gains in bone strength.…”
Section: Discussionmentioning
confidence: 96%
“…Heinonen et al [23] reported greater gains in femoral neck and spine bone mineral content in females in early puberty who participated in the exercise intervention than those who did not, but no difference was observed in females who were postpubertal. A school-based study by Meyer et al [41] included two different age groups (6-7 and 11-12 year olds) to specifically determine whether the bone response to exercise Fig.…”
Section: Do Effects Of Exercise Differ Depending On Pubertal Status Omentioning
confidence: 99%
“…Of these trials, 14 were excluded because of duplication of study populations (Table 1), and one did not present measures of variance for changes in bone outcomes [8]. Two studies had inconsistencies between tables or between tables and graphs resulting in only a fraction of the bone data being used [23,42]. Authors of two studies provided mean percent changes and SDs of percent change by sex and pubertal status for control and intervention groups because these could not be determined from the articles [41,54].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 1 more Smart Citation